Ethical issues surrounding access to care for BRCA mutations - Huang, C (2017)
Harmful BRCA (breast cancer susceptibility genes 1 and 2) mutations greatly increase women's risks of breast and/or ovarian cancer but are found in less than 1 per cent of the general population. Thus, care is targeted at women with strong family histories of breast and/or ovarian cancer. Genetic testing can determine if these high-risk women carry harmful mutations; if so, they may pursue care that facilitates cancer prevention, detection, and/or treatment. In this thesis, I examine in which cases it is problematic that some British and American women do not access this potentially life-saving care. In recognition of the difficulty in measuring access, a view informed by preliminary interviews and a literature review, I use three complementary approaches to illustrate different aspects of access. First, a critical review surveys how British and American clinical guidelines, laws, policies, and legal rulings govern service availability. Second, a scoping study describes the US and UK literature on barriers and facilitators to access. Third, an empirical study involving focus groups with UK and US genetics professionals and support group members details how women provide and pursue care. Using Beauchamp and Childress's 'four principles' framework, I analyse how these approaches inform four elements of access: availability of services, barriers to care, relevance and effectiveness of services, and equity of access. I distinguish between cases in which women do not want and/or need care and cases in which women are denied care they want and need, and I propose strategies to redress current inequities in access. I further suggest that offering Ashkenazi Jewish population screening alongside family history-based screening may be appropriate. I conclude that whilst most problematic cases are country-neutral, only US women are problematically constrained by insurance and legal loopholes, and only UK women are problematically constrained by regional variations in health authority funding.